2020
DOI: 10.1126/sciadv.aaz8534
|View full text |Cite
|
Sign up to set email alerts
|

Cystathione β-synthase regulates HIF-1α stability through persulfidation of PHD2

Abstract: The stringent expression of the hypoxia inducible factor-1α (HIF-1α) is critical to a variety of pathophysiological conditions. We reveal that, in normoxia, enzymatic action of cystathionine β-synthase (CBS) produces H2S, which persulfidates prolyl hydroxylase 2 (PHD2) at residues Cys21 and Cys33 (zinc finger motif), augmenting prolyl hydroxylase activity. Depleting endogenous H2S either by hypoxia or by inhibiting CBS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 46 publications
0
16
1
Order By: Relevance
“…Taking these observations into account, we propose that the elevated levels of CBS in BLBC could, instead, drive HIF-PH2 inactivation via persulfidation of specific Cys residues. Notwithstanding, in stark contrast to this hypothesis and our observation that CBS knockdown strongly abrogated the HIF1-α response to hypoxia, a recent study on HUVEC and HAoEC endothelial cells found that CBS inhibition stabilized HIF1-α via protecting HIF-PH2 through persulfidation of specific zinc finger domain Cys residues ( 57 ). The authors suggested that exogenous administration of H 2 S or GYY4137 (a common H 2 S donor compound) could rescue CBS inhibition–induced HIF1-α stabilization.…”
Section: Discussioncontrasting
confidence: 82%
“…Taking these observations into account, we propose that the elevated levels of CBS in BLBC could, instead, drive HIF-PH2 inactivation via persulfidation of specific Cys residues. Notwithstanding, in stark contrast to this hypothesis and our observation that CBS knockdown strongly abrogated the HIF1-α response to hypoxia, a recent study on HUVEC and HAoEC endothelial cells found that CBS inhibition stabilized HIF1-α via protecting HIF-PH2 through persulfidation of specific zinc finger domain Cys residues ( 57 ). The authors suggested that exogenous administration of H 2 S or GYY4137 (a common H 2 S donor compound) could rescue CBS inhibition–induced HIF1-α stabilization.…”
Section: Discussioncontrasting
confidence: 82%
“…Persulfidation of PHD2 at cysteine residues located in its zinc finger domain augments the interaction between PHD2 and HIF-1α, thereby promoting HIF-1α hydroxylation and degradation [ 68 ]. Treatment with GYY4137, a slow-releasing H 2 S donor, was shown to partially reverse the hypoxia-induced increase in HIF-1α protein levels and was also found to have anticancer effects in several cancer cell lines [ 68 , 69 ]. Experiments in mouse xenograft models showed that GYY4137 decreased tumor sizes without affecting the body weight or behavior of mice [ 69 ].…”
Section: Mechanisms Of Action Of Hif-1 Inhibitorsmentioning
confidence: 99%
“…Hypoxia-inducible factor (HIF)-1α is an essential transcription factor that stimulates the expression of glycolytic genes in response to hypoxia or oxidation [ 99 ]. Under normoxic conditions, CBS-dependent H 2 S inhibits prolyl hydroxylase 2, which helps target HIF-1α for degradation, thus allowing HIF-1α to accumulate and induce gene expression [ 100 , 101 ]. These important proteins regulate the expression of metabolic genes demonstrating that H 2 S can even regulate metabolism at the transcriptional level.…”
Section: Hydrogen Sulfide In Heart Metabolism and Cardiac Diseasementioning
confidence: 99%